Understanding Patient Flow from the Perspectives of Patient Movement Experts - Pieter Van Dam; Mitchell Dwyer; Malgorzata O'Reilly; Sarah Prior; James Montgomery; Richard Turner (Asia Pacific Journal of Health Management)
Background: Poor patient flow or patient movement through a healthcare organisation can lead to adverse outcomes for patients and organisational inefficiency. Many hospitals have addressed suboptimal patient flow by increasing resources, such as bed stock and staffing; however, this is an unsustainable approach. In determining the nature of poor patient flow issues, it is important to collect data from healthcare professionals who manage patient flow daily. Doing so provides insights into the current state of patient flow management in its entirety, whilst also helping with the development of sustainable solutions.